Global and diffuse solar radiant exposures at Pone (MAUSAM, 2000)
Radiation measurements are being carried out at Pune since 1957. The radiation data for the period 1986-90 are studied here with reference to general sky condition and rainfall distribution. Global irradiances show a decrease of about 5 per cent over the last four decades, The diffuse irradiation contributes about 23 per cent to the global irradiance during winter months, Its proportion increases to more than 70 per cent during the monsoon period. The specific rainfall distribution affects both global and diffuse irradiances but in opposite directions, The diffuse irradiance shows increases as the atmospheric transmission decreases, However, the changes found have not become statistically highly significant as yet.